Nutritional and functional characterisation of flour from six plantain (Musa spp.) cultivars grown in Benin - Honfo, Gbenato Fernande (My University, 2022)
Plantain flour is a promising functional ingredient of various domains in the food industry. The present work investigated the functional attributes and proximate composition of flours derived from six plantain cultivars from Benin, and evaluated their nutritional composition. Among the cultivars, proximate composition of the flours varied in moisture, ash, protein, and fibre ranging from 4.59 - 6.85, 2.01 - 2.56, 2.54 - 3.47, and 0.95 - 1.37% (dry basis), respectively. Significantly higher β-carotene contents (± 9 μg) were found in flours from Orishele and Pelipita cultivars, whereas flours from Aloga 2M and Kpahissi cultivars yielded the highest content of vitamin C (9.64 μg). Flour from Kpahissi cultivar exhibited higher water and oil absorption capacity (161.29 and 81.29%, respectively) than the other flours. In addition, higher viscosity, emulsion, and foaming capacities were recorded in flour from Kpahissi cultivar. Flours from different plantain cultivars differed in their physicochemical and functional properties, and could, therefore, be used in various food domains. In that respect, Kpahissi, Orishele, and Aloga 2M flours could be more suitable in the formulation of particular composite flour for specific uses having good functional parameters such as water and oil absorption, viscosity, emulsion, and foaming capacities.
Keywords: plantain; vitamin C; swelling power; β-carotene; viscosity